Many-body system with a four-parameter family of point interactions in one dimension - Coutinho, FAB; Nogami, Y.; Tomio, L. (Iop Publishing Ltd, 1999)
We consider a four-parameter family of point interactions in one dimension. This family is a generalization of the usual delta-function potential. We examine a system consisting of many particles of equal masses that are interacting pairwise through such a generalized point interaction. We follow McGuire who obtained exact solutions for the system when the interaction is the delta-function potential. We find exact bound states with the four-parameter family. For the scattering problem, however, we have not been so successful. This is because, as we point out, the condition of no diffraction that is crucial in McGuire's method is nor satisfied except when the four-parameter family is essentially reduced to the delta-function potential.